Comparative evaluation of ADVIA Centaur® XP chemiluminescence system for screening of HBV, HCV, HIV and syphilis in Indian blood donors. (April 2022) - Arcot, Priyadarsini Jayachandran; Pandey, Hem Chandra; Coshic, Poonam; Jain, Pankaj; Kumar, Satendra; Chakroborty, Sourit
Abstract: Background: The introduction of chemiluminescent immunoassay (CLIA) in blood donor screening has led to a gradual replacement of enzyme-linked-immunosorbent assay (ELISA) as the former offers automation, higher sensitivity and lower turn-around-time. However, only a few CLIA platforms are used for blood donor screening in India. The present study evaluated one such newer platform viz., Adiva Centaur XP CLIA for screening of HBV, HCV, HIV and syphilis. Material and methods: Prospective comparative study wherein 4843 whole blood donors were screened for HBsAg, Anti-HCV, HIV Ag-Ab and Anti-treponemal antibodies in both Advia Centaur XP and Architect i2000SR platforms. Additional tests were performed in samples which were reactive in only one of the platforms. The sensitivity, specificity, positive predictive value, negative predictive value, accuracy, false positive rate and false negative rate of both the platforms were compared. Kappa coefficient was calculated to determine the agreement between the testing platforms. Results: The sensitivity of Advia Centaur platform for HBV, HCV, HIV and syphilis detection were 94.9 %, 100 %, 100 % and 100 % respectively as compared to 96.6 %, 100 %, 100 % and 100 % in Architect i2000SR platform. The specificity of both the platforms were 99.8−99.9 % for all the four tests. The agreement between the two platforms was almost perfect for HBV, HCV and syphilis testing; and fair for HIV testing. Conclusion: The Advia Centaur CLIA platform was found to be comparable with the Architect CLIA platform for blood donor screening. Unexpected finding was the occurrence of HBV false negatives in both the platforms, possibly due to HBsAg mutations.